Secondary Immunodeficiency in Hematological Malignancies: Focus on Multiple Myeloma and Chronic Lymphocytic Leukemia - Allegra, Alessandro; Tonacci, Alessandro; Musolino, Caterina; Pioggia, Giovanni; Gangemi, Sebastiano (Frontiers in Immunology, 2021)
Secondary immunodeficiency is reported in most patients with hematological malignancies such as chronic lymphocytic leukemia and multiple myeloma. The aim of our review was to evaluate the existing literature data on patients with hematological malignancies, with particular regard to the effect of immunodeficiency on the outcome, the clinical and therapeutic approach, and on the onset of noninfectious complications such as thrombosis, pleural effusion, and orofacial complications. Immunodeficiency in these patients has an intense impact on the risk of infection in patients for whom infections are a major cause of morbidity and mortality. Moreover, it is possible that survivors after a hematological malignancy might be at increased risk of infections years after treatment completion than the general population. However, these patients with increased risk of severe infectious diseases could be treated with adequate vaccination coverage, but the vaccines' administration can be associated with a decreased immune response and an augmented risk of adverse reactions. Probably immunogenicity of the inactivated is analogous to that of healthy subjects at the moment of vaccination, but it undertakes a gradual weakening over time, and in the absence of a booster, the subjects are at risk of developing vaccine-preventable infections. However, the dispensation of live attenuated viral vaccines is controversial because of the risk of the activation of vaccine viruses. A particular immunization schedule should be employed according to the clinical and immunological condition of each of these patients to guarantee a constant immune response without any risks to the patients' health. Finally, the lack of an adequate response to the presence of a foreign antigen in the case of a self-antigen may favor the onset of a second malignancy.